Market-Oriented Ethnography: Interpretation Building and Marketing Strategy Formulation - Arnould, Eric J.; Wallendorf, Melanie (Journal of Marketing Research, 1994)
The authors show how ethnography can provide multiple strategically important perspectives on behaviors of interest to marketing researchers. They first discuss the goals and four essential characteristics of ethnographic interpretation. Then they review the particular contributions to interpretation of several kinds of ethnographic observation and interview data. Next they discuss how interpretations are built from ethnographic data. They show how multilayered interpretations of market phenomena emerge through systematic analysis of complementary and discrepant data. Finally, the authors articulate three representational strategies that are used to link multilayered interpretations to marketing strategy formulation. They suggest that ethnographic methods are appropriate for apprehending a wide variety of consumption and use situations with implications for market segmentation and targeting; product and service positioning; and product, service, and brand management.